Normal laboratory reference intervals among healthy adults screened for a HIV pre-exposure prophylaxis clinical trial in Botswana. - Tebogo M Segolodi (Public Library of Science (PLoS), 2014)
Introduction Accurate clinical laboratory reference values derived from a local or regional population base are required to correctly interpret laboratory results. In Botswana, most reference intervals used to date are not standardized across clinical laboratories and are based on values derived from populations in the United States or Western Europe. Methods We measured 14 hematologic and biochemical parameters of healthy young adults screened for participation in the Botswana HIV Pre-exposure Prophylaxis Study using tenofovir disoproxil fumarate and emtricitabine (TDF/FTC) (TDF2 Study). Reference intervals were calculated using standard methods, stratified by gender, and compared with the site-derived reference values used for the TDF2 study (BOTUSA ranges), the Division of AIDS (DAIDS) Grading Table for Adverse Events, the Botswana public health laboratories, and other regional references. Results Out of 2533 screened participants, 1786 met eligibility criteria for participation in study and were included in the analysis. Our reference values were comparable to those of the Botswana public health system except for amylase, blood urea nitrogen (BUN), phosphate, total and direct bilirubin. Compared to our reference values, BOTUSA reference ranges would have classified participants as out of range for some analytes, with amylase (50.8%) and creatinine (32.0%) producing the highest out of range values. Applying the DAIDS toxicity grading system to the values would have resulted in 45 and 18 participants as having severe or life threatening values for amylase and hemoglobin, respectively. Conclusion Our reference values illustrate the differences in hematological and biochemical analyte ranges between African and Western populations. Thus, the use of western-derived reference laboratory values to screen a group of Batswana adults resulted in many healthy people being classified as having out-of-range blood analytes. The need to establish accurate local or regional reference values is apparent and we hope our results can be used to that end in Botswana.